Response of tomato to innovative organo-mineral fertilizers - Sitzmann, Tomas Javier; Alpigiano, Andrea; Lerda, Cristina; Moretti, Barbara; Zavattaro, Laura; Grignani, Carlo (Frontiers in Sustainable Food Systems, 2024)
Organo-mineral fertilizers (OMFs) with low organic carbon (Corg) content have been associated with higher mineral fraction nutrient use efficiency. However, the extraction of peat, which is typically used in these OMFs, from endangered ecosystems causes long-time stored Corg to mineralize and to be released back into the atmosphere as carbon dioxide (CO2). This study analyzes the replacement of peat in OMFs with biowaste materials. These materials, considered organic byproducts that microorganisms and other living things can decompose through composting and aerobic or anaerobic digestion, offer a viable opportunity. This study investigated three stabilized biowastes—green compost (GC) from pruning residues, municipal solid waste compost (MSWC), and manure-based vermicompost (VC)—as the organic matrices for granular OMFs. These matrices were impregnated with dissolved ammonium sulfate and urea and used to coat diammonium phosphate granules. Each biowaste OMF contained 7.5% Corg, 20% mineral N, and 10% mineral P2O5 (OMF20 − 10). Fertilizers with high nutrient concentrations have the advantage of requiring low application volumes, facilitating their application in the field. Biowaste OMFs were compared with peat OMFs with the same Corg-N-P2O5 concentration. Peat and MSWC were also used to create OMFs containing 7.5% Corg, 10% mineral N, and 5% mineral P2O5 (OMF10 − 5). A 75-day tunnel trial was conducted under semi-controlled conditions using tomato plants (Solanum lycopersicum L.) fertilized to an equivalent of 81 mg N kg−1 soil and 18 mg P kg−1 soil. Controls included no fertilization (N0P0) and mineral N and P fertilization (MFNP). The Soil Plant Analysis Development (SPAD) chlorophyll meter and the BBCH (from German Biologische Bundesanstalt, Bundessortenamt und CHemische Industrie) scale as well as the number of shoots were measured over time, as berry and total aboveground yield, N and P uptakes, and N and P use efficiencies (NUE and PUE, respectively) were calculated at harvest. All treatments outperformed the control N0P0 in most indicators. Peat20 − 10 did not have more berry yield than other OMF20 − 10; however, the higher number of shoots indicated a higher potential yield in the event of prolonging the experiment. At the end of 75 days, VC20 − 10 and MSWC20 − 10 showed similar PUE to peat, suggesting that those materials can be used as replacements. In the case of OMF10 − 5, MSWC10 − 5 had yield and N and P uptakes like peat OMFs, confirming the potential use of MSWC as peat replacement even at different nutrient concentrations. This research provides reassuring evidence of the effectiveness of biowaste OMFs, offering a positive outlook for sustainable agriculture. However, their use is not recommendable for short growing seasons.